Feeding value of buckwheat silage for lamb as compared to maize silage - Keles G.; Kocaman V.; Ustundag O.; Ozdogan M. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
The alternative forages resources could help alleviating feed scarcity and improve the sustainability of ruminant production. Thus, the present study was carried out to investigate the feeding value of buckwheat (Fagopyrum esculentum Moench.) silage for feedlot lambs as an alternative forage source. Buckwheat harvested at the end of the milk stage was ensiled in 40 kg plastic bags after wilting and chopping. A total of 18 early weaned (2.5-3 month) Karya male lambs divided into two groups and were individually fed total mixed diets that either contains buckwheat or maize silage at dry matter (DM) proportions of 0.50 in isonitrogenous and isoenergetic diets. At the end of 63 d experiment, lambs fed the diet containing buckwheat silage had 7.6% higher DM intake (P<0.05) than the lambs fed the diet containing maize silage. However, live weight gain and feed efficiency was similar (P>0.05) for both lambs that were fed either buckwheat silage or the maize silage. No period x diet interaction was detected (P>0.05) for the DM and nutrient intake. The results indicated that the feeding value of buckwheat was similar or even higher than the maize silage
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)